From Colonial Castaways to Current Tribulation: Tragedy of Indian Hijra - Singh, Amit Kumar (Unisia, 2022)
This article analyses the current human rights situation of hijras (eunuchs) in India against the background of Criminal Tribes Act (CTA) in 1871. This article argues that British colonial construct/imposition of masculinity on Indian hijras by classifying them as ‘criminal tribes’ have adversely impacted their lives not only in British India, but also in Contemporary India. To support main argument, article also contextualizes gender theories in the light of hijra’s bodies.